The Effectiveness of Problem Based Learning (PBL) with Open-Ended Approach on Problem Solving Ability (Universitas Negeri Semarang, 2019)
This study has the purpose of analyzing the effectiveness of the Problem Based Learning (PBL) model with the Open-Ended approach on students' problem-solving abilities. This type of study was an experimental research with a non-equivalent pre-test – post-test control group design. The population of the study was grade IV students of Elementary School in Cluster of Jenderal Sudirman, Kebonagung District, Demak Regency in 2018/2019. Samples were taken by using a random sampling technique. Problem-solving ability as a dependent variable. And the Open-Ended approach as an independent variable. The method was used as an essay test item. The data analysis techniques were using Validity, Reliability, Difficulty test, Normality test, Homogeneity test, t-test, and N-gain test. Problem-solving ability can be improved by applying the PBL model with the open-ended approach. This can be shown based on the results of N-gain test is the average value of an experimental group is higher than the control group (0.7029 > 0.5118). The average N-Gain problem-solving ability of students taught using the PBL model with Open-Ended approach is higher than average N-Gain problem-solving ability of students taught using the PBL model.